The agenda setting power of news media in framing the future role of tourism in protected areas. (October 2017) - Schweinsberg, Stephen; Darcy, Simon; Cheng, Mingming
Abstract: This exploratory paper examines the agenda-setting and framing role of news media in the ongoing development of the Draft Sydney Royal Botanic Gardens and Domain Trust Master Plan. The paper will argue that the publication of the Masterplan and ensuing public commentary has drawn into stark focus future challenges in juxtaposing the frames of public use, commercial tourism and scientific/cultural values in the sustainable management of protected areas. Agenda setting and framing theory provides the theoretical foundation for the paper. Guided by critical discourse analysis, the analysis of the paper is supported through the use of Leximancer and Gephi software for visually illustrating the relationship between different framing perspectives. This paper contributes to a fresh understanding of the complex nature of the sustainable management of protected areas in urban spaces. Highlights: Historical formulation of tourism in the Royal Botanic Gardens, Sydney. Leximancer software to identify themes in community responses to Royal Botanic Gardens and Domain Trust Masterplan. Visualized stakeholder network presents a clear network of each stakeholder's perceived position in the debate. Placement of newspaper framing of tourism in an urban protected area sustainability context.